PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI KELAS XI SMA NEGERI SEKAMPUNG TAHUN PELAJARAN 2018/2019 - Sundari Sundari; Ningrum Ningrum; Tiara Anggia Dewi (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2021)
As for the problem in the research conducted by researchers, “ there are still many students who have not experienced learning completeness in the learning outcomes of the XI SMA Negeri 1 Sekampung in the academic year 2018/2019”. Based on these problems, the problem statement is, Is there a positive influence on the use of cooperative learning model type example non example on learning outcomes in economic subjects in class XI SMA Negeri 1 Sekampung in the academic yaer 2018/2019 ?The purpose of this study was “ to find out the effect of using cooperative learning models for example non example types on learning outcomes in economic subjects in class XI of SMA Negeri 1 Sekampung in the academic year 2018/2019. Based on the results of the research conducted, the hypothesis is accepted, because the value of tcount> t table can be seen in the appendix list G, at a significance level of 5%, namely 9,50> 1.70. Students who are declared complete with KKM are (72) after being given treatment with the inside outside circle model which is as many as 25 students or with a percentage of 83,33% and those that are not complete are 5 students with a percentage of 16,67%. Thus it shows that the Cooperative Learning Model Type Example Non Example has a positive influence on the economic learning outcomes of class XI students of State High School 1 Sekampung Academic Year 2018/2019.